Design of W‐band sheet beam travelling wave tubes based on staggered double vane slow wave structure. Issue 14 (13th June 2018) - Tian, Hanwen; Shao, Wei; Wang, Zhanliang; Wei, Yanyu; Duan, Zhaoyun; Gong, Yubin; Feng, Jinjun
Abstract : In this study, a complete and viable plan about a W‐band sheet beam travelling wave tube based on a staggered double vane slow wave structure is drawn up. The dispersion characteristics, transposition characteristics of high‐frequency system, sheet electron beam gun, vacuum window, periodically cusped magnetic focusing system and beam–wave interaction are analysed by CST Microwave Studio, CST Particle Studio and HFSS. An attenuator is used in this device to suppress oscillation. A phase velocity taper is used to increase output power. The operation voltage is 20.6 kV and the current is 80 mA. With a 10 W input power, the output power is 1100 W versus the gain is 20.41 dB at 95 GHz. The peak amplitude approaches 1200 W versus the gain approaches 20.79 dB at 99 GHz.